Pengujian Device dan Blackbox pada Aplikasi Augmented Reality Alat Musik Tradisional Yogyakarta - Nuri Cahyono; Ramadhan Bima Saputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One of Indonesia's provinces, D.I. Yogyakarta is rich in regional culture and arts, including traditional musical instruments, traditional weapons, and houses.Traditional musical instruments are one of Yogyakarta's typical local cultures.Traditional musical instruments are now a specialty of the province, especially in Yogyakarta, where Javanese culture is still strong and well-known.Concern for the preservation of national culture, particularly traditional musical instruments, has diminished significantly over time.One important reason for people's growing interest in Yogyakarta's culture is, for instance, the community's lack of exposure to and familiarization with it. Using Android-based Augmented Reality (AR) technology is one method for introducing younger generations to Yogyakarta traditional musical instruments. From 2D objects, users can directly view information, sound, and 3D objects with this technology.As a result, the researcher was motivated to develop an Android app that would teach students about a variety of Yogyakarta traditional musical instruments through the use of augmented reality. This application was developed using the Unity and Vuforia SDK software as libraries and C# as the programming language. In this study utilizing the MDLC (Multimedia Development Live Cycle) Multimedia Development Method which is limited only to the testing stage then in carrying out the testing using the Blackbox method as a method of testing the functionality of the applications that have been made.